Integral Methods in Science and Engineering 2013
DOI: 10.1007/978-1-4614-7828-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solutions of the 1D Convection–Diffusion–Reaction and the Burgers Equation Using Implicit Multi-stage and Finite Element Methods

Abstract: In the last decades, developments in computational mechanics motivated extensive research on numerical solutions that had an important impact on society [OdEtAl03]. In particular, we are interested in procedures that can be adapted to problems involving convective, diffusive, and reactive processes. These problems have a vast applicability (see [GoCoCa00], [TaShDe07], [KuEsDa04]), such as the simulation of pollution effects in rivers; modeling of the evolution of oil and natural gas reserves in the underground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…So, the m-step iterative method ATC has m+1 convergence order and it requires that the nonlinear function F(·) should have at least three Fréchet derivatives. Note that wide classes of important ODEs and PDEs, such as those arising in the Bratu problem, the Frank-Kamenetzkii problem [12], the Lene-Emden equation [13], the Burgers equation [14], the Klein-Gordon equation [15], the two-dimensional sinh-Poisson equation [16], and the three-dimensional nonlinear Poisson equation [17], heat equation, wave equation, Euler's beam equation etc., give rise to F(x) functions with high order Fréchet derivatives. Then, the multi-step iterative method ATC is applicable to wide classes of important problems.…”
Section: Convergence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…So, the m-step iterative method ATC has m+1 convergence order and it requires that the nonlinear function F(·) should have at least three Fréchet derivatives. Note that wide classes of important ODEs and PDEs, such as those arising in the Bratu problem, the Frank-Kamenetzkii problem [12], the Lene-Emden equation [13], the Burgers equation [14], the Klein-Gordon equation [15], the two-dimensional sinh-Poisson equation [16], and the three-dimensional nonlinear Poisson equation [17], heat equation, wave equation, Euler's beam equation etc., give rise to F(x) functions with high order Fréchet derivatives. Then, the multi-step iterative method ATC is applicable to wide classes of important problems.…”
Section: Convergence Analysismentioning
confidence: 99%
“…Several numerical methods have been proposed recently for approximating the solution of (11)- (14) such as the homotopy method [19], the finite difference method [20,21], and the variational iteration method [22]. Also, Bao et al [23] suggested some high-accurate numerical methods for solving numerically (11)- (14).…”
Section: The Nonlinear Complex Generalized Zakharov Systemmentioning
confidence: 99%
See 1 more Smart Citation